BTN3A Targeting Vγ9Vδ2 T Cells Antimicrobial Activity Against Coxiella burnetii-Infected Cells - Gay, Laetitia; Mezouar, Soraya; Cano, Carla; Foucher, Etienne; Gabriac, Mélanie; Fullana, Marie; Madakamutil, Loui; Mège, Jean-Louis; Olive, Daniel (Frontiers in Immunology, 2022)
Vγ9Vδ2 T cells have been reported to participate to the immune response against infectious diseases such as the Q fever caused by Coxiella burnetii infection. Indeed, the number and proportion of Vγ9Vδ2 T cells are increased during the acute phase of Q fever. Human Vγ9Vδ2 T cell responses are triggered by phosphoantigens (pAgs) produced by pathogens and malignant cells, that are sensed via the membrane receptors butyrophilin-3A1 (BTN3A1) and -2A1 (BTN2A1). Here, by using CRISPR-Cas9 inactivation in THP-1 cells, we show that BTN3A and BTN2A are required to Vγ9Vδ2 T cell response to C. burnetii infection, though not directly involved in the infection process. Furthermore, C. burnetii-infected monocytes display increased BTN3A and BTN2A expression and induce Vγ9Vδ2 T cell activation that can be inhibited by specific antagonist mAb. More importantly, we show that the antimicrobial functions of Vγ9Vδ2 T cells towards C. burnetii are enhanced in the presence of an BTN3A activating antibody. This supports the role of V9V2 T cells in the control of C. burnetii infection and argues in favor of targeting these cells as an alternative treatment strategy for infectious diseases caused by intracellular bacteria.